IMS キカンチュウ ニ エラレタ ショウワキチ シュウヘン ノ チジキ タテン カンソク データ カイセキ ケッカ オーロラ ジェットデンリュウ イチ ト オーロラ ハッコウイキ トノ ヒカク オヨビ ナンボク チジキ キョウヤクセイ ノ ヘンドウ - 鮎川, 勝; アユカワ, マサル; 巻田, 和男; マキタ, カズオ; Ayukawa, Masaru; Makita, Kazuo (1998)
P(論文) 国際地球磁気圏観測計画(IMS, 1976-1978)期間中に, 昭和基地周辺でオーロラ活動に伴う超高層物理現象の地上多点観測を実施した。この地上多点観測で得られた地磁気の変動記録に基づきオーロラジェット電流(auroral electrojet current)位置とオーロラ発光領域の対応関係, 地磁気H成分が湾型負変動(negative bay variation)している時の南北共役性及び地磁気共役点の日変化特性などを解析した。その結果, 電離層中に水平電流を仮定した時, (1) 地磁気Z成分変動から求めたΔZ=0の地点がオーロラの活動的な発光領域のほぼ真下に位置し, オーロラジェット電流は極域電離層の比較的狭い領域を集中的に流れている。(2) 地磁気H成分の湾型負変動時の南北共役性に関しては, 北半球側のレイルボグル(Leirvogur, Iceland)と最も良い相互相関を示す地点は, みずほ基地よりも低緯度側の無人観測点や昭和基地であった。(3) 南北共役性の日変化は, 北半球側の共役点(南半球の共役点を固定した場合)は夕方側から真夜中側(18h-00h MLT)にかけて高緯度側に, 真夜中側から朝方側(00h-08h MLT)にかけて低緯度側にシフトする地方時依存特性を示し, この特性はTsyganenko-Usmanovのモデルによる共役点の日変化パターンの傾向と一致する。 This report describes the movement of small scale auroral electrojet current regions and their relationships to spatial and temporal variation of visual auroras based on magnetic data at three ground stations [Syowa (69°00′S, 39°36′E, 30m a. s. l.), Unmanned (69°47′S, 41°35′E, 1470m a. s. l.) and Mizuho (70°42′S, 44°20′E, 2230m a.s.l.)]. Japanese Antarctic Research Expedition (JARE) party carried out this observation as a contribution to the International Magnetospheric Study (IMS) from 1976 to 1978. It was shown that ionospheric currents with no change in Z-component magnetic field variations corresponded to auroral luminous regions. This result suggests that the line current approximation is applicable to small scale auroral electrojet currents. Secondary, a conjugacy of polar substorm phenomena is examined with comparing magnetogram data obtained from three ground stations in Antarctica and with those from Leirvogur station (64°08′N, 21°47′W), Iceland in the northern hemisphere. During quiet periods, the conjugacy could not be identified due to poor correlation of magnetic field variations between Leirvogur and the three stations in Antarctica. On the other hand, during disturbed periods, the conjugate point of Leirvogur was located near the Unmanned station. Thirdly, the diurnal variation of magnetic conjugate point is examined with magnetogram data of antarctic three ground stations and two stations ...